Development of the personnel management system under the conditions of digital transformations - Shmatko, Nataliia M.; Karminska-Bielobrova, Maryna V.; Kostin, Vadym O.; Bielobrova, Anita O. (Національний технічний університет "Харківський політехнічний інститут", 2025)
The article is devoted to studying the impact of digital transformations on human resource management systems in modern organizations. The growing role of digital technologies in the HR field is driving fundamental changes in recruitment, training, performance evaluation, employee motivation, and career development processes. The relevance of the research is determined by the need for organizations to adapt to new conditions and seek modern approaches to human resource management to improve their efficiency and competitiveness. The paper analyzes key issues faced by human resource management systems, including insufficient automation, low employee engagement, communication barriers, and a lack of professional development programs. The main areas of HR process digitalization are identified, including the implementation of analytics platforms (People Analytics), learning management systems (LMS), recruitment platforms (LinkedIn, Workday), and other tools that allow automation and optimization of HR functions. Special attention is given to the prospects and trends of digitalization in Ukraine, where many organizations show high adaptability to the adoption of innovative technologies. The authors also present recommendations for implementing digital HR management systems. In particular, for effective digital transformation, it is necessary to assess the organization's readiness for change, choose appropriate technologies integrated with existing systems, and provide training to staff to improve digital literacy and reduce resistance to change. These measures significantly improve the efficiency of human resource management systems, reduce costs, improve communication between employees, and ensure continuous employee development. The article also points out that the implementation of digital technologies is associated with certain challenges, such as high integration costs, data privacy risks, and the need to restructure organizational culture. Despite these challenges, the benefits of HR digitalization far outweigh the potential drawbacks, creating opportunities for strategic business development. The results emphasize the importance of a comprehensive approach to the digital transformation of human resource management systems, which enables organizations to remain competitive in a dynamic business environment.

Стаття присвячена дослідженню впливу цифрових трансформацій на систему управління персоналом у сучасних організаціях. Зростання ролі цифрових технологій у сфері HR спричиняє докорінні зміни в процесах рекрутингу, навчання, оцінки ефективності, мотивації персоналу та кар'єрного зростання. Актуальність дослідження обумовлена необхідністю адаптації організацій до нових умов і пошуку сучасних підходів до управління людськими ресурсами для підвищення їхньої ефективності та конкурентоспроможності. У роботі аналізуються ключові проблеми, що стоять перед системами управління персоналом, зокрема недостатня автоматизація, низький рівень залученості співробітників, комунікаційні бар'єри та дефіцит програм професійного розвитку. Визначено основні напрями цифровізації HR-процесів, які включають впровадження аналітичних платформ (People Analytics), систем для управління навчанням (LMS), платформ для рекрутингу (LinkedIn, Workday) та інших інструментів, що дозволяють автоматизувати і оптимізувати HR-функції. Особлива увага приділена перспективам і трендам цифровізації в Україні, де багато організацій демонструють високу адаптивність до впровадження інноваційних технологій. Автори також висвітлюють рекомендації щодо впровадження цифрових систем управління персоналом. Зокрема, для ефективної цифрової трансформації необхідно здійснювати оцінку готовності організації до змін, вибирати відповідні технології, інтегровані з існуючими системами, і проводити навчання персоналу для підвищення цифрової грамотності та зменшення опору змінам. Ці заходи дозволяють значно підвищити ефективність систем управління персоналом, знизити витрати, поліпшити комунікацію між співробітниками та забезпечити безперервний розвиток персоналу. У статті також зазначено, що впровадження цифрових технологій пов'язане з певними викликами, такими як висока вартість інтеграції, ризики порушення конфіденційності даних та необхідність перебудови організаційної культури. Попри це, переваги цифровізації HR значно перевищують можливі недоліки, створюючи перспективи для стратегічного розвитку бізнесу. Отримані результати підкреслюють важливість комплексного підходу до цифрової трансформації системи управління персоналом, яка дозволяє організаціям залишатися конкурентоспроможними у динамічному бізнес-середовищі.
Розвиток системи управління персоналом за умов цифрових трансформацій
Keywords: HR digitalization; human resource management; analytics platforms; recruitment; employee training; digital transformation; цифровізація HR; управління персоналом; аналітичні платформи; рекрутинг; навчання персоналу; цифрова трансформація